Enhancing household disaster preparedness among older adults using the N-TORM intervention: A quasi-experimental study in rural Indonesia - Diki Ardiansyah; Roviatul Imaniah; Rita Fitri Yulita; Susilawati Susilawati; Asep Badrujamaludin; Khrisna Wisnusakti; Firman Sugiharto (Nursing and Health Sciences Journal (NHSJ), 2026)
Older adults in earthquake-prone low- and middle-income countries (LMICs) face disproportionate disaster-related morbidity and mortality. Culturally adapted, nurse-led preparedness programs for this demographic in seismically active LMIC settings remain largely unexplored. This study evaluated the effectiveness of the Nurses Taking on Readiness Measures (N-TORM) intervention on household emergency preparedness (HEP) among older adults (≥ 60 years) residing near Indonesia’s Lembang Fault. A quasi-experimental, non-equivalent control-group pre-post design was implemented in April 2025 in Suntenjaya Village, West Java. Forty participants were allocated to intervention (n = 20) or control (n = 20) groups based on residential clusters to minimize contamination. The six-day N-TORM intervention comprised disaster education, booklet-guided planning, and home-visit monitoring. HEP was measured using the 32-item Household Emergency Preparedness Instrument (HEPI; score range 32–160; ≥ 112 indicates preparedness). Data were analyzed using the Wilcoxon signed-rank and Mann-Whitney U tests. Baseline assessments categorized both groups as unprepared (median HEPI score: 57). Post-intervention, the intervention group showed a significant increase in score (median: 126, p < 0.001), successfully achieving the prepared threshold. The control group exhibited no significant change. Between-group comparisons at post-test revealed a highly significant difference (Mann-Whitney U = 0.00, p < 0.001). The culturally adapted N-TORM intervention significantly enhances household emergency preparedness among older adults in earthquake-prone LMICs. Integrating such nurse-led programs into existing community health infrastructure, particularly integrated health posts, offers a scalable strategy to strengthen disaster risk reduction for vulnerable aging populations.